Reducing isocyanate exposure and asthma risk in motor vehicle repair. Issue 4 (9th November 2015) - Piney, Mark; Llewellyn, Diane; O'Hara, Rachel; Saunders, John; Cocker, John; Jones, Kate; Fishwick, David
Abstract : Purpose: – Exposure to isocyanates was the leading cause of occupational asthma in the UK. Motor vehicle repair (MVR) bodyshop paint sprayers were at greatest risk, despite widespread use of air-fed breathing apparatus and ventilated booths. Most paint sprayers work in small and medium enterprises (SMEs). The purpose of the Health and Safety Executive (HSE) project, described in this paper, is to improve exposure control measures in at least 20 per cent of MVR bodyshops, and reduce the risk of occupational asthma. The paper aims to discuss this issue. Design/methodology/approach: – A three-stranded plan consisted of: Safety and Health Awareness Days (SHADs); workplace inspections; and third-party stakeholder communications. The impact of various parts of the project were evaluated. Findings: – Approximately 18 per cent of bodyshops in the UK attended one of 32 SHADs, following which over 90 per cent of delegates expressed an "intention to act" to improve exposure control measures. A local assessment showed that at least 50 per cent of bodyshops improved exposure control measures. An evaluation of 109 inspections found that enforcement action was taken at 40 per cent of visits. Third-party engagement produced a joint HSE-industry designed poster, new agreed guidance on spray booths and dissemination of SHAD material. Knowledge of booth clearance time has become widespread, and 85 per cent of booths now have pressure gauges. Biological monitoring data show that, post-SHAD, exposures were lower. Originality/value: – A sustained national project using clear, relevant, tested messages delivered via different routes, had a sector-wide impact in bodyshops. It is probable that the project has improved isocyanate exposure control in at least 20 per cent of bodyshops. The generic lessons could be applied to other widespread SME businesses.